Biooxazolidines‐Enabled Improvement of Monocomponent Polyurethane Coatings. Issue 2 (15th November 2021) - Song, Xinyan; Lin, Yinlei; Zhu, Chenjing; Huang, Jianhui; Bai, Xiaoxu; Zhang, Haichen; Hu, Huawen; Li, Guangji
Abstract: Single‐component moisture‐cured polyurethane (SPU) possesses the merit of easy preparation and high curing efficiency but suffers from poor apparent properties, mechanical performance, and thermal stability. Herein, the authors employ isophorone diisocyanate (IPDI) and 2‐isopropyl‐3‐hydroxyethyl‐1, 3‐oxazolidines (IHO) to synthesize oxazolidine (termed as IPDI‐IHO) for the subsequent modification of SPU. The structure and composition of the synthesized SPU/IPDI‐IHO composites are unraveled by 1 H and 13 C NMR and FTIR spectroscopies. Apart from the curing properties of SPU/IPDI‐IHO, the apparent properties, mechanical performance, thermal stability, and self‐healing ability are evaluated. SEM and AFM characterizations reveal that IPDI‐IHO incorporation significantly decreased the number of bubbles and thus reduce the SPU‐based sample surface roughness. The thermal stability of SPU is notably improved after IPDI‐IHO modification. The tensile strength and elongation at break also increases from 830 to 3710 kPa and from 210% to 600%, respectively, due to IPDI‐IHO inclusion, with the optimal mechanical properties achieved at the IPDI‐IHO mass ratio of 8 wt%. Furthermore, the cracks intentionally cut for the SPU/IPDI‐IHO sample can be self‐healed at 60 °C. The ensemble of the performance enhancements suggests that the IPDI‐IHO developed in this work opens up a new route to fabricate high‐performance SPU and related polymeric materials. Abstract : The biooxazolidines (IPDI‐IHO) is synthesized to be employed as a promising curing agent and a valuable additive for the design and fabrication of highly performing SPU‐based composite materials.